2023
DOI: 10.3390/ani13081388
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Protocols for the Assessment of Anti-Tick Compounds from Pinus roxburghii against Rhipicephalus (Boophilus) microplus Ticks

Abstract: Pinus roxburghii, also known by the name “Himalayan chir pine,” belongs to the Pinaceae family. Rhipicephalus (Boophilus) microplus tick is one of the most significant bovine ectoparasites, making it a major vector of economically important tick-borne diseases. The researchers conducted adult immersion tests (AIT) and larval packet tests (LPT) to investigate the acaricidal effect of P. roxburghii plant extract on R. (B.) microplus and its potential modulatory function when used with cypermethrin. Eggs were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…The same was the case for S. scabiei mites, whose mortality was also time-and dose-dependent. These results are in line with the findings of [37,38], in which the mortality effect of botanicals was indicated to be dose-, concentration-and exposure-time-dependent. Our study also revealed that all methanolic extracts of the tested botanical leaves at the tested concentrations induced a significant acaricidal effect against S. scabiei mites and R. microplus compared with the negative control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The same was the case for S. scabiei mites, whose mortality was also time-and dose-dependent. These results are in line with the findings of [37,38], in which the mortality effect of botanicals was indicated to be dose-, concentration-and exposure-time-dependent. Our study also revealed that all methanolic extracts of the tested botanical leaves at the tested concentrations induced a significant acaricidal effect against S. scabiei mites and R. microplus compared with the negative control.…”
Section: Discussionsupporting
confidence: 92%
“…The extracts efficacy against R. microplus ticks was determined using the adult immersion test (AIT) and larval packet test (LPT) according to the protocol outlined by Ayub et al, [37] and Matos et al [44]. The tick's larval mortality was recorded at 24 and 48 h for different concentrations.…”
Section: Adult Immersion Test and Larval Packet Testmentioning
confidence: 99%
“…Ticks and mites were treated with different concentrations of the ethanol extracts. Previous studies have explored the acaricidal properties of various herbs against mites and ticks [13,30,47,48]. C. sinensis has been reported to possess antioxidant [49], antibacterial [50], anti-inflammatory, and antihistaminic properties [51], as well as insecticidal properties [52], whereas no acaricidal potential of the plant has been documented.…”
Section: Discussionmentioning
confidence: 99%